Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.21608/adjalexu.2019.57360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Raloxifene in the Prevention of Osteoporosis of Alveolar Bone Induced by High Fat Diet in Rats

Abstract: INTRODUCTION: Obesity is positively associated with many chronic disorders such as osteoporosis, as it decreases the osteoblastic cell formation, increases the osteoclastic activity and decreases the vascularity of the bone marrow as well. Raloxifene belongs to a class of drugs called selective estrogen receptor modulators (SERMs). It reduces the expression of bone turnover markers and increases bone mineral density. OBJECTIVES: To investigate the effect of Raloxifene in the prevention of osteoporosis of alveo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The histopathological findings of the MO treated group revealed a noticeable improvement in bone microarchitecture resembling normal histology of mandibular alveolar bone in rats as described by Ezzat et al, Montaser et al and Sherif et al [18,37,38]. This comes in accordance with Patel et al who studied the MO leaf extract treatment at 200mg/kg bodyweight on (OVX) rats for 30 days.…”
Section: Soliman T Et Alsupporting
confidence: 85%
See 1 more Smart Citation
“…The histopathological findings of the MO treated group revealed a noticeable improvement in bone microarchitecture resembling normal histology of mandibular alveolar bone in rats as described by Ezzat et al, Montaser et al and Sherif et al [18,37,38]. This comes in accordance with Patel et al who studied the MO leaf extract treatment at 200mg/kg bodyweight on (OVX) rats for 30 days.…”
Section: Soliman T Et Alsupporting
confidence: 85%
“…Concerning the histomorphometric analysis, the bone area percent values increased in the MO treated group and approached the normal values in healthy rats as reported by Ezzat et al and Montaser et al [18,37]. Ei Behairy et al also had supporting results where the histomorphomeric analysis showed the highest mean value of bone area percent in the MO leaf powder aqueous extract injected at extraction site in dogs [41].…”
Section: Soliman T Et Almentioning
confidence: 52%